Loss of tetraspanin‐7 expression reduces pancreatic β‐cell exocytosis Ca2+ sensitivity but has limited effect on systemic metabolism. Issue 12 (31st October 2022) - McLaughlin, Kerry; Acreman, Samuel; Nawaz, Sameena; Cutteridge, Joseph; Clark, Anne; Knudsen, Jakob G.; Denwood, Geoffrey; Spigelman, Aliya F.; Manning Fox, Jocelyn E.; Singh, Sumeet Pal; MacDonald, Patrick E.; Hastoy, Benoit; et al.
Abstract: Background: Tetraspanin‐7 (Tspan7) is an islet autoantigen involved in autoimmune type 1 diabetes and known to regulate β‐cell L‐type Ca 2+ channel activity. However, the role of Tspan7 in pancreatic β‐cell function is not yet fully understood. Methods: Histological analyses were conducted using immunostaining. Whole‐body metabolism was tested using glucose tolerance test. Islet hormone secretion was quantified using static batch incubation or dynamic perifusion. β‐cell transmembrane currents, electrical activity and exocytosis were measured using whole‐cell patch‐clamping and capacitance measurements. Gene expression was studied using mRNA‐sequencing and quantitative PCR. Results: Tspan7 is expressed in insulin‐containing granules of pancreatic β‐cells and glucagon‐producing α‐cells. Tspan7 knockout mice (Tspan7 y/− mouse) exhibit reduced body weight and ad libitum plasma glucose but normal glucose tolerance. Tspan7 y/− islets have normal insulin content and glucose‐ or tolbutamide‐stimulated insulin secretion. Depolarisation‐triggered Ca 2+ current was enhanced in Tspan7 y/− β‐cells, but β‐cell electrical activity and depolarisation‐evoked exocytosis were unchanged suggesting that exocytosis was less sensitive to Ca 2+ . TSPAN7 knockdown (KD) in human pseudo‐islets led to a significant reduction in insulin secretion stimulated by 20 mM K + . Transcriptomic analyses show that TSPAN7 KD in human pseudo‐islets correlated with changes in genes involved in hormone secretion, apoptosis and ER stress. Consistent with rodent β‐cells, exocytotic Ca 2+ sensitivity was reduced in a human β‐cell line (EndoC‐βH1) following Tspan7 KD. Conclusion: Tspan7 is involved in the regulation of Ca 2+ ‐dependent exocytosis in β‐cells. Its function is more significant in human β‐cells than their rodent counterparts.